Examining university student’s motivational factors and preferences for job choice - Vafnóczki, Attila József (Studia Mundi – Economica, 2025)
In the changing labour market of the 21st century, it is crucial to understand the motivational factors, drivers and preferences that university students formulate in the face of their prospective employers, as they are the ones who will soon dictate the new trends when entering the labour market. The majority of students who are now in a student-worker relationship are born into Generation Z, and differ in many aspects and personality traits from members of previous generations. They have a different appreciation of themselves and the world around them, different values and different attitudes towards work and their future employers. Many aspects of the labour market challenges of the past decades are changing, and most HR managers are now looking for solutions to these challenges, when in fact the right guidance should be provided to students on the university bench, making life easier for both sides. In the questionnaire survey, 171 university students from almost all counties of Hungary were interviewed, and nearly 75% of them identified themselves as Generation Z. In addition to demographic questions, I also asked about their motivational factors and preferences, their expected net income, and their migration intentions. In addition to these, I examined what kind of assistance they currently receive as students in their educational institution in relation to their choice of job. 59% of students have some intention to migrate, 71% have not yet participated in a dual training or apprenticeship programme, and then 60% said that they either had not gained knowledge and experience of preparing for the world of work or, if they had, they did not feel sufficiently prepared.